TINGKAT PENGETAHUAN WANITA PEKERJA SEKS KOMERSIAL DAN PERILAKU PENCEGAHAN PENULARAN HUMAN IMMUNODEFICIENCY VIRUS DI PAGUYUBAN BUNGA SEROJA YOGYAKARTA - Wenny Savitri; Dikki Setiyawan; Sri Purwaningsih (Fakultas Ilmu Kesehatan, 2016)
Human Immunodeficiency Virus (HIV) is a virus which damages immune system in the human body that can lead to death. The virus can be transmitted by sexual activity. Evidence shows that HIV prevalence among sex workers is 12 times greater than among the general population. Bunga Seroja Community is a social community consists of female sex workers in Yogyakarta, Indonesia. This community arranges programs to promote health of female commercial sex workers to prevent HIV/AIDS including health education, psychosocial support, routine health check-up, and many other activities. Scientific study is needed to see the correlation between the knowledge of female commercial sex workers, who have been exposed regularly with positive environment (Bunga Seroja Community), with their behaviour to prevent HIV/AIDS infection.A descriptive correlation study, involving 36 female commercial sex workers was taken place at Bunga Seroja Community in Yogyakarta, Indonesia. Questionnaires consisted of 21 questions of information regarding HIV/AIDS and 20 questions to find out the respondents’ behaviour in preventing HIV infection were used. The data were then analyzed by using Kendall Tau statistical analysis.The study revealed that most respondents had high level of knowledge (77.8%) and positive behaviour regarding prevention of HIV infection (88.9%).Kendall Tau analysis showed the coefficient value of correlation was 0.663 (p<.05). It shows that there is strong correlation between the level of knowledge of the female commercial sex workers in Bunga Seroja Community with their behaviour in preventing HIV infection. Keywords: HIV, AIDS, knowledge, behaviour.